Discovery of novel antagonists of glycoprotein IIb/IIIa-mediated platelet aggregation through virtual screening. Issue 6 (15th March 2015) - Wang, Yawen; Zhao, Yang; Sun, Rui; Kong, Wanjun; Wang, Bing; Yang, Guangde; Li, Yiping
Graphical abstract